Practical Fuzzy-CAC Realization for Effective Traffic Engineering in MPLS-TE Networks - Jelinskis, J.; Skrastins, A.; Lauks, G. (Elektronika ir Elektrotechnika, 2011)
In this investigation the new Fuzzy-CAC algorithm practical implementation of RSVP-TE protocol development for use in MPLS-TE/GMPLS networks is presented. Fuzzy-CAC algorithm is tested on the MPLS-TE network testbed with 3 Cisco 2800 series routers, on which classical threshold CAC algorithm is compared to the Fuzzy-CAC algorithm implementation. Main QoS characteristics are analyzed, experimental data are depicted and future research subjects are described. Ill. 14, bibl. 9, tabl. 4 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.281